Effect of kangaroo method care accompanied by mozart classical music therapy on weight gain in LBW babies at H. Abdul Manan Simatupang Hospital Kisaran 2023 - Ika Lestari Sitorus; Juliana; Usti Fina Hasanah Hasibuan (Science Midwifery, 2023)
Kangaroo method care is a method of care by caring for the baby in a naked state (only wearing diapers and hats) placed upright/vertical on the chest between the two breasts of the mother (mother bare chest) then covered (Triana et al, 2015). This research method uses the Quasi-Experimental method, with the design of One Group Pretest-Posttes Without Control. The population of this study amounted to 20 LBW babies using a purposive sampling technique. The research instrument used an observation sheet. Data analysis techniques using descriptive analysis and chi-square test. The results of the study There is an effect of the kangaroo method accompanied by Mozart classical music therapy on increasing body weight in LBW babies at HAMS Hospital Kisaran in 2023 with a p-value = 0.000 (p <0.05). These results prove that the kangaroo method accompanied by Mozart classical music therapy is proven to influence increasing the body weight of LBW babies at HAMS Hospital in Kisaran in 2023. It is concluded that there is an effect of the kangaroo method accompanied by Mozart's classical music on increasing the weight of LBW babies. Suggestions for this study are expected to health services and health workers, especially midwives, are expected to provide education and practice about the kangaroo method accompanied by Mozart classical music to increase the weight of LBW babies and are expected to be a consideration for midwifery services to make music therapy as an obstetric intervention.